My dear Henry : a Jekyll & Hyde remix - Bayron, Kalynn (Remixed classics., 2023)
"In this reimagination of Dr. Jekyll and Mr. Hyde, a teen boy tries to discover the reason behind his best friend's disappearance and the arrival of a mysterious and magnetic stranger"--